Analysis of terahertz double dielectric structure patch antenna using nitride semiconductors. Issue 1 (11th February 2023) - Miura, Shin; Kurahashi, Kenta; Goshima, Keishiro; Nagase, Masanori
Abstract: Recently, gallium arsenide (GaAs)‐based resonant tunneling diode (RTD) oscillators and indium phosphorus (InP)‐based Schottky barrier diode (SBD) receivers have been studied in the terahertz (THz) band. The THz devices for practical use should operate at room temperature, be small in size, and have high output power. Therefore, this study was focused on gallium nitride (GaN), which possesses excellent material properties, such as wide bandgap characteristics and heteroepitaxy on Si substrates. The GaN‐based oscillators and receivers are expected to be compact, operate at room‐temperature, and act as a high‐power device for the THz‐band devices. However, GaN has crystal defects, which can cause instability in device operations. A double dielectric structure patch antenna composed of Silicon Nitride (SiN) and Benzo Cyclo Butene (BCB) with different dielectric constants was proposed to realize a GaN‐based THz transmitter and receiver. The antenna characteristics were investigated using the Finite Difference Time Domain (FDTD) method. The results showed that the SiN has little effect on the radiation, whereas the BCB is strongly responsible for the radiation. Comparing the absolute gain between the double dielectric structure and the conventional structure using the SiN, it was confirmed that the double dielectric structure can improve the absolute gain.